English Language Learning Inside and Outside the Classroom in Portugal - Tonoian, Lilit (2014)
This study investigates the way of learning the English language in Portugal. First-year students of the faculty of Social Sciences and Humanities of New University of Lisbon were selected as participants in the case study. As data collection tools a questionnaire and focus-groups were used. 115 students completed the designed questionnaire and after that 12 students were selected for the more detailed focus-group discussions. Results of the research show that most part of the students´ English knowledge is received from outside the classroom by means of movies, songs, computer games, the Internet, communication with friends and other sources. Also, the results show that motivation is very important in language learning process and motivated students acquire the language faster and easier.